The Effectiveness of Flipped Classroom in Improving Students' Learning Outcomes - I Gusti Ayu Dewi Paramita; Evin Yudhi Setyono; Ni Nyoman Yuliantini; Ni Ketut Suciani (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
An appropriate learning method is a basic way for learners to be able to achieve maximum grades and the achievement of existing learning objectives. The Flipped Classroom method is one of the new methods in Indonesia which can be one of the preferred methods that can be applied in teaching English. Surely, a trial is required to measure its effectiveness. The current study has two purposes, the first one was to determine whether the Flipped Classroom learning method was able to effectively improve student learning outcomes, especially in English lectures. Then, secondly, the purpose was how to apply Flipped Classroom in the classroom. This research is quantitative descriptive research with a quasi-experimental approach, employing a